Pengembangan Game Wordwall untuk Menstimulasi Angka Anak Usia Dini - A’yun, Arina Khifata; Widjanarko, Paulus; Setiawan, M.Hery Yuli (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to develop the Wordwall game as a learning medium to stimulate number recognition skills in early childhood and to determine the feasibility of the developed medium. The background of this study is based on children’s low ability to recognize number symbols and the lack of interactive learning media in the classroom. This study employed the Research and Development (R&D) method using the 4D model, which includes the define, design, develop, and disseminate stages. The study was conducted at the Mumtazul Ilmi Banjarsari Kindergarten with 12 children aged 5–6 years as research subjects. Data collection techniques included observation, interviews, and documentation, while the research instruments consisted of observation sheets and an expert validation questionnaire. Data analysis was conducted using both quantitative and qualitative methods to determine the media’s suitability and children’s responses to its use. The research findings indicate that the Wordwall game-based learning media was deemed suitable for use based on the validation results from subject matter experts and media experts, following several improvements to its visual and audio aspects. Additionally, the results of a limited pilot study indicate that the use of the Wordwall game can enhance children’s engagement, motivation, and active participation in learning. This media also helps children learn numbers more easily through interactive, visual, and enjoyable activities. Thus, the Wordwall game can serve as an innovative and effective alternative learning tool for stimulating number recognition skills in early childhood